Issues of the enterprises competitiveness growth in the framework of the Eurasian Integration. - Akhmetov, D. (Journal of Economic Research & Business Administration, 2015)
Eurasian integration is a project of the independent post-Soviet states union with a single political, economic, military, customs, humanitarian and cultural space, intended to be created by the CIS member countries on the basis of the respective integration structures. All the members of the Eurasian integration designed to develop a clear and concise strategy of action, having as its ultimate goal the creation of an innovative economy. This will allow them to get out of the status of “peripheral exporters of raw materials” and take a worthy place in the world “division of labor”. Thatis why the questions of the competitiveness of Kazakh enterprises within the Eurasian integration are very important.